Overcoming Consumer Resistance to AI in General Health Care. Issue 2 (May 2023) - Gaczek, Piotr; Pozharliev, Rumen; Leszczyński, Grzegorz; Zieliński, Marek
Artificial intelligence (AI) in medicine offers a unique opportunity to improve the global health system. However, consumers remain skeptical about AI's ability to accurately assess their medical condition. The five studies here provide insights into consumers' reluctance to use AI-produced health care recommendations. Consumers are less willing to follow a medical recommendation from AI (vs. from a human) when the medical diagnosis provides health results that are good (i.e., symptoms do not require medical care) versus bad (i.e., symptoms are worrisome and may require urgent care) (Study 1a). The effect is mediated by consumers' perception of diagnosis trustworthiness (Study 1b) and enhanced by consumers' health anxiety score (Study 2). Providing social proof (e.g., number of satisfied customers recommending the service) reduces the negative effect of health anxiety on consumers' trust in the medical diagnosis and increases their willingness to follow the AI's recommendations (Study 3a). The findings provide insights into the psychological drivers of acceptance of automated health care and suggest possible actions to overcome consumers' reluctance to follow AI medical recommendations.